DIGITAL TRANSFORMATION OF BUSINESS MANAGEMENT: INNOVATIVE MODELS, FORECAST SCENARIOS AND CURRENT CHALLENGES OF ECONOMY MODERNIZATION - Burtnyak , I.V.; Khaludilo , T.V. (The actual problems of regional economy development, 2025)
The theoretical foundations of digital transformation in enterprise management have been substantiated in the article under conditions of dynamic market changes and globalization. It has been demonstrated that the traditional model of managerial processes and certain measures for the implementation of digital technologies are conflicted with contemporary challenges—global economic crises, tensions in international relations, and the rapid development of information technologies—which reduces enterprises’ ability to adapt to external shocks. The aim of the study has been defined as the systematization and deepening of the theoretical basis for digital transformation in management from the standpoint of integrating artificial intelligence, machine learning, big data analytics, and cloud services for the modernization of the economy and the enhancement of business competitiveness. The principal barriers to the implementation of digital technologies within management systems have been identified by the authors, and effective approaches for their overcoming have been proposed in order to ensure the stability and flexibility of managerial decisions. General scientific methods—abstraction, analysis, synthesis, logical generalization, and comparison—have been employed in the work. The stages of transition from traditional approaches to digital models have been examined through functional analysis in the context of societal reproduction—production, distribution, exchange, and consumption—while a historical review of the evolution of management thought has been combined with an analysis of contemporary practices. Key aspects of digitalization, including the integration of innovative technologies into management systems, the utilization of computer algorithms for processing large volumes of data, and the creation of interactive platforms for prompt decision-making, have been examined in the article. Special attention has been paid to external factors – global crises, international‐political challenges, and internal structural changes within companies. The scientific novelty has been constituted by the development of a functional concept of digital transformation in management, which takes into account the influence of both external economic conditions and internal innovation processes on enterprises’ adaptability. The results obtained are expected to contribute to increased forecasting accuracy, accelerated responsiveness to external changes, and strengthened competitiveness of enterprises.